2007
DOI: 10.1353/dem.2007.0023
|View full text |Cite
|
Sign up to set email alerts
|

Self-selection and earnings assimilation: Immigrants from the former Soviet Union in Israel and the United States

Abstract: Drawing on U.S. decennial census data and on Israeli census and longitudinal data, we compare the educational levels and earnings assimilation of Jewish immigrants from the former Soviet Union (FSU) in the United States and Israel during 1968-2000. Because the doors to both countries were practically open to FSU immigrants between 1968 and 1989, when FSU immigrants were entitled to refugee visas in the United States, the comparison can be viewed as a natural experiment in immigrants' destination choices. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 18 publications
4
73
0
Order By: Relevance
“…Immigrants in the US do not represent a random sample of the population from the countries of origin (Borjas, 1987). Some immigrant groups are positively self-selected on their observed characteristics, as evidenced by the high educational levels of US immigrants from India and countries in Africa (Cohen & Haberfeld, 2007;Portes & Rumbaut, 1996), while some immigrant groups are negatively self selected on observed characteristics, such as the lower educational attainment of US immigrants from Mexico. Since previous studies have shown different types of self-selection in immigrants, discussions in this paper are applicable to overseas communities of the Indians and Chinese, rather than the Indians and Chinese in general.…”
Section: Migration and Ethnic Entrepreneurshipmentioning
confidence: 99%
“…Immigrants in the US do not represent a random sample of the population from the countries of origin (Borjas, 1987). Some immigrant groups are positively self-selected on their observed characteristics, as evidenced by the high educational levels of US immigrants from India and countries in Africa (Cohen & Haberfeld, 2007;Portes & Rumbaut, 1996), while some immigrant groups are negatively self selected on observed characteristics, such as the lower educational attainment of US immigrants from Mexico. Since previous studies have shown different types of self-selection in immigrants, discussions in this paper are applicable to overseas communities of the Indians and Chinese, rather than the Indians and Chinese in general.…”
Section: Migration and Ethnic Entrepreneurshipmentioning
confidence: 99%
“…Immigrants arriving from the Soviet Union and other countries in Eastern Europe, Africa and Asia were of higher educational levels than their predecessors coming from the same countries in the 1950s and 1960s. True, during the 1970s and early 1980s, Jewish emigrants from the FSU that reached the U.S. were of higher educational levels than those coming to Israel (DellaPergola 1986;Cohen and Haberfeld 2007). But, apparently, Israel of the post-1967 period became a more attractive destination for educated immigrants.…”
Section: Source Countries and Patterns Of Immigrants' Self-selectionmentioning
confidence: 99%
“…Interestingly, Jewish immigrants from the FSU who arrived during the 1990s to Canada (Lewin-Epstein et al 2003) or the U.S. (DellaPergola 1998;Cohen and Haberfeld 2007) were of higher educational levels than their counterparts who came to Israel; however, those arriving to Germany in the 1990s were of similar educational level to those coming to Israel Kogan 2005, 2007). In short, in the competition for educated immigrants from the FSU, Israel performed rather well versus Germany, but lost to the U.S. and Canada.…”
Section: Recent Changes In Migration Patternsmentioning
confidence: 99%
“…Focusing on the self-selection of immigrants in terms of education, which also leads to earnings' assimilation as well as it is correlated with health, Cohen and Haberfeld (2007) compared immigrants from the former Soviet Union (FSU) to Israel and to the United States, during the time period of . During this period of the Cold War, the United States opened its doors to FSU immigrants, granting them refugee visas.…”
Section: Introductionmentioning
confidence: 99%